2018
DOI: 10.1101/463141
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Subthalamic nucleus and sensorimotor cortex activity during speech production

Abstract: The sensorimotor cortex is somatotopically organized to represent the vocal tract articulators, such as lips, tongue, larynx, and jaw. How speech and articulatory features are encoded at the subcortical level, however, remains largely unknown. We analyzed local field potential (LFP) recordings from the subthalamic nucleus (STN) and simultaneous electrocorticography recordings from the sensorimotor cortex of 11 patients (1 female) with Parkinson's disease during implantation of deep brain stimulation (DBS) elec… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 75 publications
(87 reference statements)
1
8
0
Order By: Relevance
“…Studies using more sophisticated methods, such as articulography [ 42 ] or speech signal processing [ 43 ], might reveal even more insights about the potential benefits of aDBS. In addition to this, other activities in the STN LFP or biomarkers from the motor cortex could be used to monitor speech articulation, in order to further improve the efficacy of aDBS [ 44 ]. However, this is yet to be tested.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using more sophisticated methods, such as articulography [ 42 ] or speech signal processing [ 43 ], might reveal even more insights about the potential benefits of aDBS. In addition to this, other activities in the STN LFP or biomarkers from the motor cortex could be used to monitor speech articulation, in order to further improve the efficacy of aDBS [ 44 ]. However, this is yet to be tested.…”
Section: Discussionmentioning
confidence: 99%
“…Significant increases in broadband gamma activity began before but were predominantly locked to speech onset. Given that broadband gamma activity is thought to index synchronized local neuronal firing (25,26) and is associated with the functional activation of relevant brain regions during a wide range of sensorimotor and cognitive tasks, including speech and language processing (11,16,(27)(28)(29), our data suggest that the ventral lateral thalamus tracks speech production.…”
Section: Discussionmentioning
confidence: 85%
“…We recently developed a protocol to study subcortical activity during single-syllable word/nonword reading, in patients undergoing DBS lead implantation (15,16). Here, we explore whether the thalamus participates in the encoding of lexical status, by recording local field potentials (LFP) in patients undergoing DBS lead implantation for essential tremor targeting the ventral intermediate nucleus of the thalamus (Vim, which corresponds to the ventral portion of the ventral lateral posterior nucleus (VLp) (17)).…”
Section: Introductionmentioning
confidence: 99%
“…Recent work suggested that the subthalamic nucleus (STN) is also involved in speech production. Increased activity in the gamma band in the STN was shown before speech onset and during articulation, similar to the sensorimotor cortex ( 14 ). In fact, DBS of the STN can alleviate specific speech symptoms like hypophonia and voice tremor ( 15 ).…”
Section: Introductionmentioning
confidence: 97%